The world of tattoo : an illustrated history - van Dinter, Maarten Hesselt (Amsterdam : KIT, 2005)
Introduction ## Destructive Western influences ## Limited research ## The origin and functions of tattoos ## Current trends in the West ## 1. EUROPE ## Archaeological finds -- Asian influences -- Greek and Roman punitive tattoos -- Britannia, land of the painted people -- Christian practices in the Middle Ages -- Rediscovery by explorers -- Growth of tattooing among criminals and prostitutes -- Japanese influence on high society -- The emancipation of the tattoo ## 2. CHINA AND JAPAN ## An indicator of low social status in China -- The flowering of decorative tattoo art in Japan -- Cultural heritage sidelined ## 3. SOUTHEAST ASIA ## Sexual motifs in trouser tattoos -- Magical tattoos of animals and gods -- Tribal traditions of Chinese islands -- Piercing and tattooing on the Philippines -- Tattooed weaving patterns ## 4. INDONESIA ## Borneo : inspiration for new tribalism -- Elegant lines and curves on Mentawai -- Burn marks as signs of male courage ## 5. INDIA ## Tattoos as Hindu caste markings -- Headhunting mountain tribes ## 6. OCEANIA ## Polynesia -- The advance of European animal motifs -- Warlike grooves and spirals -- Trouser tattoos versus the missionaries -- Geometric figures and mourning tattoos -- Melanesia -- Women as living jewels -- Stylised figures and sexual designs -- Micronesia -- A prohibition on tattoos and grass skirts -- Religious ceremonies and youthful trends ## 7. MIDDLE EAST ## Disseminated by gypsies and Bedouins -- Beauty spots and passages from the Koran ## 8. AFRICA ## Discrete dots in the Maghreb -- Ancient Egyptian tattooing traditions -- Scar tattoos in Black Africa ## 9. LATIN AMERICA ## Warrior tattoos in middle America -- Caribbean cults -- Pre-colonial traditions in the Amazon region -- Decorated women in the Gran Chaco “# 10. NORTH AMERICA ## Decorative tattoos -- Warrior symbols and marks of honour -- Clan totems ## 11. ARCTIC ## A question of life and death for the Inuit -- Decorations for male courage in Siberia.
Includes bibliographical references (p. [275]-290) and index.
boek